(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The present investigation was to quantify and characterize the chemical profile of bioactive components of stem bark of Adansonia digitata using GC-MS and HPLC analysis. The plant stem bark were extracted using three solvents, the bioactive components of each solvent were characterize using Gas chromatography mass spectrometry (GC MS) analysis and High performance liquid chromatography (HPLC) analysis. The GC MS analysis revealed the chemical profile of the extract with different compounds with distinct peaks, retention time (RT), molecular formular, molecular weight, chemical structure and area%. Nineteen (19) components were identified in petroleum ether, Twenty two (22) components were identified in ethanol and twenty two (22) components were identified in aqueous. The HPLC analysis shows different compounds with distinct peaks and their retention time. The analysis reveal major phytochemicatcals like Triterpenoids, alkaloids, fatty acids, vitamins and etc. The presence of various bioactive compounds confirms the use of stem bark extract of Adansonia digitata for various ailments by Herbal system of medicine. Further study is recommended in order to isolate, identify and purified each of the bioactive constituents present in the stem bark of Adansonia digitata to yield a pure compounds that can be packaged in to orthodox drugs